ISOLASI, KARAKTERISASI BAKTERI ASAM LAKTAT, DAN ANALISIS PROKSIMAT DARI PANGAN FERMENTASI RUSIP IKAN TERI (Stolephorus sp.) - Deverina Mergypta; Anto Budiharjo; Endang Kusdiyantini (Jurnal Akademika Biologi, 2014)
Rusip is a traditional food from Bangka-Belitung made from fresh anchovy with salt and palm sugar that is brooded for seven days. Rusip fermentation process is caused by microbial activity mainly from lactic acid bacteria. The purpose of this study was to isolate lactic acid bacteria from rusip, to characterize isolates obtained based on common characteristic of lactic acid bacteria, and to carry out proximate analysis of rusip anchovy. Isolation from rusip fermented food obtained eight bacterial isolates, five isolates were circular and three isolates were rod-shaped. Characterization and identification of lactic acid bacterial were performed using tests that led to the common characteristic of lactic acid bacteria, i.e the gram staining, motility test, acid formation test, catalase test, and proteolytic test. The result showed that eight bacterial isolates were gram-positive, non-motile, catalase-negative, positive to produce acid, and had proteolytic activity. Rusip anchovy had 0,64% of total lactic acid and the pH 5,40. Nutrient content of rusip fermentation had 10,3644% moisture content; 50,0702% ash content; 0,9524% crude fat content; 0,3764% crude fiber content; 34,8603% crude protein content; and 14,1171% carbohydrate content. Keywords: rusip, isolation, characterization, lactic acid bacteria, proximate analysis